Review of the elements influencing job satisfaction on job performance, with quality of work life as mediating in the Jordanian hotel industry - Fazida, Karim; Mahadzirah, Mohamad; Bandar Ersan, Alown (2020)
The hotel industry is a major pillar of tourism because of the services it provides in the field of the national economy, as a result of the funds it pumps, and as a means of obtaining the foreign currency necessary to implement the comprehensive development plans in the countries of the world. This paper aims to examine the factors influencing the job performance of the Jordanian hotel industry. This study relied on the theoretical approach by reviewing the theoretical literature and previous studies related to the variables of the study. A survey of previous studies and theories related to the subject of the study was conducted. Many factors have been disregarded in numerous writing in light of job satisfaction and job performance, and in view of the survey discoveries; there is a positive connection between organisation structure, leadership style, job satisfaction, quality of work-life, and job performance. The present paper proposed to the hotel industry to the firm-up interconnection between job satisfaction, quality of work-life, and job performance. It similarly enumerated equally theoretical and practical ramifications based on earlier writing and suggested future studies to concentrate more on the factors affecting job performance in Jordanian hotels.